INFORMAL TRADE IN THE MARKETS MARIANO BORJA AND THE HOPE OF RIOBAMBA, A DESCRIPTIVE STUDY - Donoso Valdivieso, Marcelo; Aucancela Guamán, Margarita; Haro Sosa, Giovanny; Naranjo Vaca, Myriam (mktDESCUBRE; Vol 1 No 2 (2020): Special Edition 3rd International Scientific Congress of Administrative and Financial Sciences FADE 2019, 2020)
One of the activities that the ONEM research group has been carrying out is the study of informal commerce in the city of Riobamba. To this end, a survey was applied to the informal merchants of the Condamine market (clothes sellers), todetermine their profile and some characteristics of their economic activity. The type of sampling is non- probabilistic and the number of surveys was 117